Nambu-Poisson dynamics (Archives of Mechanics - Test, 1998)
Several physical systems can be described by using multibrackets instead of the usual Poisson or Jacobi brackets. Starting with the original construction of Nambu we give a brief review on recent results on multibrackets on manifolds.